What Dimension of Meaning in Life is the Stronger Predictor of Borderline Personality Disorder Symptom?. Issue 4 (2nd October 2021) - Lorca, Fátima; Pérez, Sandra; Giner, Francesc; Marco, José H.
Abstract: Researchers seem to view meaning in life as consisting of different dimensions: coherence, purpose, and significance. Meaning in life has been found to be a protective factor against several mental disorders, and an association between meaning in life and the psychopathology of Borderline Personality Disorder (BPD) has been found. The aim of this study is to analyze the role of the dimensions of meaning in life. The sample was composed of 102 participants with BPD diagnoses from mental health services in Spain, and all of them filled out the BSL-23, PIL-10, MLQ, and OLQ questionnaires. The results suggest that BPD symptoms are negatively correlated with meaning in life. The meaning in life dimensions' model accounted for 52% of the variance in BPD symptoms. The variables that significantly predicted BPD symptoms were: Meaning and Satisfaction, Comprehensibility (coherence), and Purpose and Vital Goals. The present study emphasizes meaning in life as an important variable in BPD psychopathology.